Pengenalan Nilai Gizi Ikan-Ikan Danau Sentani kepada Masyarakat Asli Sentani di Kampung Yoboi, Kabupaten Jayapura, Papua - Henderite L. Ohee; Sarni R. A. Bela; Lidia G. S. R. Ohee; Miranti M. Sroyer; Johan G.M. Sanadi; Selly R. Andeina; Leony V. D. Maisorry (LPPM Uncen, 2026)
Fish have traditionally been the main source of protein for indigenous communities living around Lake Sentani. The fish include both endemic and introduced species. However, despite frequent consumption, community knowledge regarding the nutritional composition of these fish remains limited, even though they are generally perceived as highly nutritious and beneficial. In response, this community service program sought to provide information on the nutritional value of native fish species from Lake Sentani, as well as non-native species. The program was implemented in Yoboi Village on May 18, 2025, using lecture and interactive discussion methods with two target groups: adolescents and adults of both sexes. The adolescent session consisted of a presentation followed by a question-and-answer discussion, with participants’ knowledge evaluated through pre- and post-tests. The adult session followed a similar approach, emphasizing the nutritional benefits of local fish species. Results from the adolescent group revealed a moderate level of understanding, indicating the need for continued education to strengthen awareness of the importance of fish consumption. Overall, fish constitute a vital source of high-quality protein that should be regularly included in the diet of all age groups, from children to adults.